2012
DOI: 10.1186/1471-2318-12-18
|View full text |Cite
|
Sign up to set email alerts
|

Radical cystectomy over the age of 75 is safe and increases survival

Abstract: BackgroundRadical cystectomy (RC) is probably underused in elderly patients due to a potential increased postoperative complication risk, as reflected by their considerable comorbidities. Our objective was to estimate the overall complication rate and investigate a potential benefit to patients over the age of 75 subjected to RC in terms of disease-free survival.MethodsA total of 81 patients, 61 men and 20 women, from two urological departments, with a mean age of 79.2 ± 3.7 years, participated in the study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
2
3
0
1
Order By: Relevance
“…Careful follow-up surveillance is therefore recommended in the first 90 days after RC. This has also been noted by Donat et al [23] and Tyritzis et al [13]. The average time of hospitalization between American and European patients was as follows: the European time of hospitalization was between 10 and 90 days (mean 24, median 21) and the American one was between 2 and 51 days (mean 11, median 9 days).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Careful follow-up surveillance is therefore recommended in the first 90 days after RC. This has also been noted by Donat et al [23] and Tyritzis et al [13]. The average time of hospitalization between American and European patients was as follows: the European time of hospitalization was between 10 and 90 days (mean 24, median 21) and the American one was between 2 and 51 days (mean 11, median 9 days).…”
Section: Discussionsupporting
confidence: 54%
“…Large contemporary series with an average age of approximately 63 years show complication rates of 24-61% and 90-day mortality rates of approximately 10-37% [1,13]. Due to increased comorbidities, decreased physiological reserve and decreased ability to respond to stressors, elderly patients have an increased risk of complications [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…As elderly patients generally have more comorbid conditions, RC is often judged too risky by urologists . However, several studies have suggested that RC in octogenarians is underused and inappropriately denied .…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple reports have advocated RC in the elderly and demonstrated that in selected older patients the outcomes are similar to younger patients . Furthermore, some reports have gone further and showed that RC is safe and effective even in high‐risk elderly patients with significant comorbidities .…”
Section: Introductionmentioning
confidence: 99%
“…Äàííûå, îïèñàííûå ðàíåå â ìèðîâîé ëèòåðàòóðå, ñâèäåòåëüñòâóþò î áîëåå âûñîêèõ ïîêàçàòåëÿõ ïåðèîïåðàöèîííûõ îñëîaeíåíèé ïîñëå ÎÐÖÝ ó ïîaeèëûõ ïàöèåíòîâ [21,22]. Îäíàêî äàííûé ôàêò (âëèÿíèå âîçðàñòà ïàöèåíòîâ íà ðàííèå è îòäàëåííûå ðåçóëüòàòû ÐÖÝ) â äàëüíåéøèõ èññëåäîâàíèÿõ íå áûë ïîäòâåðaeäåí.…”
unclassified